PSYCHOLOGICAL FEATURES OF COPING STRATEGIES CHOICE UNDER MARTIAL LAW BY STUDENTS - Литвинчук, Наталія; Римарчук, Аліна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article is devoted to the problem of coping strategies choice under martial law by students. The Aim of study was to define coping strategies connection with situational and personal anxiety level and students type of locus of control. There were used such methods for researching the stated problem: method «Coping-test» (Richard S. Lazarus); method " Scale of self-assessment of situational and personal anxiety level” (Charles Spielberger, Yuriy Khanin); method of locus of control research (ulian Rotter); methods of mathematical statistics: Spearman correlation. The article analyzes the concepts “coping strategies”, “anxiety”, “locus of control”. The factors that determine an individual's choice of certain coping strategies in a stressful situation areindicated. There were determined psychological factors promoting successful psychological-social adaptation in stressful situations and helping solve problems effectively, these are: stress resistance, conviction, responsibility, resilience, optimal level of anxiety, adequate self-esteem, willpower, internal locus of control, optimism, self-confidence, positive self-attitude, value-meaning structures of personality, empathy, developed communication skills. The importance of health, individuals toughness and strong social connections giving a sense of belonging, support and understanding was emphesized. Results. It was found that coping strategies of more than half of respondents have an average level of expression, which indicates a satisfactory adaptive potential of students. The most common strategies were: “Escape/Avoidance” (60%), “Social Support Seeking” (55%), “Positive Reappraisal” (55%), “Self-Control” (52%). At the same time, low levels of rates were observed on the “Acceptance of Responsibility” scale (30%). According to method " Scale of self-assessment of situational and personal anxiety level” of Charles Spielberger and Yuriy Khanin it was found that most of students demonstrate a hign level of both situational anxiety (52%) and personal anxiety (65%). According to the results of method of locus of control, it was found that 37% of students have a predominantly internal type of control, 50% - a predominantly external one. A combination of both characteristics types was found in 13% of respondents. Conclusions. According to the results of the research it was stated that situational anxiety has a direct connection with coping strategy “Acceptance of Responsibility”. It was also discovered that personal anxiety is correlated with strategies "Planning a problem-solving" and "Taking responsibility." A significant correlation was found between “locus of control” and coping strategy "Distancing". It was found that coping strategy "Distancing" has a direct connection with externality and an inverse connection with internality. It is concluded that there was not found any connection with another scales. Key words: coping strategy; locus of control; students; anxiety; martial law.